Biology and Behavior of Microlarinus lareynii Jacq. a Curculionid bioagent of Tribulus terrestris L. (Damascus University Journal of agriculture sciences, 2021)
Biology and behavior of a Curculionid bioagent, Microlarinus lareynii Jacq.  attacking the cosmopolitan weed, puncturevine, Tribulus terrestris L. was carried out at Biological Control Studies and Research Centre, Faculty of Agriculture, Damascus University during 2013-2016. Female oviposited exclusively in top site of the fruits, in holes in one chamber, almost 50 % of the fruits were infested by one egg. The length of egg was 0.51 - 0.72 (av. 0.58) mm and width 0.45 - 0.56 (av. 0.49) mm. Incubation period in laboratory was 3-5 (av. 3.56) days. Last larval stage was stout, fleshy and curved with body length ranged from 3.29 to 4.95 mm with an average of 4.31 mm. The entire larval development completed within 15-25 (av. 20.32) days, the hatched larva feed on the fruit tissues and tunneled it and penetrate one or two chambers of the fruit. Pupation occurred inside infested fruits and this stage lasted for 3-6 (av. 4) days. The weevil length was 3.12 - 4.55 (av. 3.86) mm. The plant carried 105 - 320 (av. 128.16) fruits and the number of infested fruits by the weevil, was 45- 116 av. (76.12) fruits with an infestation percentage 34.43 to 43.36 (av. 39.3) %. The fully grown adults hibernate in November in debris under the plant canopy.